1989
DOI: 10.1159/000261182
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Laser and Fluoride on Acid Resistance of Human Dental Enamel (with 1 color plate)

Abstract: Specimens of human dental enamel were topically applied with solutions of sodium fluoride (NaF) or acidulated phosphate fluoride (APF) before and after laser irradiation. APF application after laser irradiation caused a remarkable increase in acid resistance of the enamel, while APF application before laser irradiation showed a lesser effect, similar to either APF treatment alone or laser irradiation alone. These results were consistent with observations made using a scanning electron microscope. APF applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2
16

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(109 citation statements)
references
References 16 publications
4
87
2
16
Order By: Relevance
“…Laser irradiation associated to the fluor, is also efficient in the increase of the enamel resistance (Twasi et al, 1991), and in the increase of the fluor incorporation (Tagomori & Morioka, 1989), being able to play an important role in the prevention or removal of dental caries (White et al).…”
Section: Discussionmentioning
confidence: 99%
“…Laser irradiation associated to the fluor, is also efficient in the increase of the enamel resistance (Twasi et al, 1991), and in the increase of the fluor incorporation (Tagomori & Morioka, 1989), being able to play an important role in the prevention or removal of dental caries (White et al).…”
Section: Discussionmentioning
confidence: 99%
“…Besides CO 2 -lasers, which had originally been used for this purpose [1][2][3][4][5][6][7][8][9][10] to reduce the acid dissolution of enamel, other lasers have been investigated in laboratory studies including Nd:YAG, [11][12][13][14] Er:YAG-, [15][16][17][18] and Er,Cr:YSGG-, [19][20][21] as well as argon ion lasers [22][23][24][25][26][27][28] with and without additional topical fluoride application. There are also reports from small scale in vivo studies using an argon laser around orthodontic brackets 29 or Nd:YAG-laser treatment coupled with initiation dye and acidulated fluoride application in children with the effects assessed by following the development of white spot lesions or fissure caries.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies over the past thirty years have indicated that lasers can be used to thermally modify the chemical composition of dental enamel to render it more resistant to acid dissolution and potentially more resistant to dental caries [24][25][26][27][28][29][30] . Moreover, other studies have indicated that topical fluoride treatments can work synergistically with the laser treatment to further enhance its inhibitory effect [31][32][33][34] . However, it has yet to be demonstrated that lasers can be used to inhibit the demineralization of dentin and only a few papers have identified any beneficial effect of laser treatments on dentin 35,36 .…”
Section: Author Manuscriptmentioning
confidence: 99%